Improvement of Bioconversion of Vitamin D3 into Calcitriol by Actinomyces hyovaginalis through Protoplast Fusion and Enzyme Immobilization - M. Abbas, Ahmad; M. Aboshanab, Khaled; F. Elkhatib, Walid; M. Aboulwafa, Mohammad; A. Hassouna, Nadia (International Journal of Biotechnology for Wellness Industries, 2017)
Protoplast fusion and enzyme immobilization techniques were applied to increase calcitriol production from vitamin D3 using Actinomyces hyovaginalis, a local isolate recovered from Egyptian soil, that has a potential bioconversion activity of vitamin D3 into calcitriol. A total of sixteen protoplast hybrids, formed between Actinomyces hyovaginalis isolate and two Bacillus species (B. thuringiensis and B. weihenstephanensis) were screened for vitamin D3 bioconversion activity. Compared to wild type isolate, four hybrids (formed between Actinomyces hyovaginalis isolate and B. thuringiensis) were found to preserve the bioconversion activity; out of which, three hybrids coded V2B, V3B and V8A exhibited higher calcitriol production. The hybrids coded V2B and V8A produced, per 1 L culture medium, about 0.5 and 0.4 mg calcitriol corresponding to 350% and 280%, respectively, increase compared to the wild type isolate. Among different alginate concentrations applied, immobilization of cell lysate of Actinomyces hyovaginalis isolate using 2% alginate showed 140% increase in calcitriol production from vitamin D3 compared to the free cell lysate. Activity of the immobilized form was preserved for five repetitive uses over a period of 15 days but with a 50% decline in production occurring at the fifth use.